2021
DOI: 10.1002/ccr3.4948
|View full text |Cite
|
Sign up to set email alerts
|

Hair regrowth and maintenance in alopecia universalis patient treated with nonablative Er:YAG laser

Abstract: Hair regrowth with no adverse effects following nonablative 2940-nm Er:YAG laser treatment in alopecia universalis patient resulted in high patient satisfaction and compliance. As the main challenge in alopecia universalis is maintenance of regrown hair, patient compliance associated with this treatment might represent an advantage over traditional treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, all such studies are conducted in animal models. Finally, a case report of significant hair regrowth in a patient with alopecia universalis following treatment with nonablative Er:YAG laser treatment, PRP, and exosome injections has been described 53 . Further definitive research is required in human clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…However, all such studies are conducted in animal models. Finally, a case report of significant hair regrowth in a patient with alopecia universalis following treatment with nonablative Er:YAG laser treatment, PRP, and exosome injections has been described 53 . Further definitive research is required in human clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several groups have demonstrated that microneedling may be effective in treating AGA ( 24 ) and AA ( 25 ). Both ablative and non-ablative settings of Er:YAG lasers have been used in AGA and AA, with promising results ( 26 28 ).…”
Section: The Immune System Interaction With the Hair Follicle Nichementioning
confidence: 99%
“…7 Traditional treatments, that is, finasteride and minoxidil, have not shown the ability to reverse the fate of terminal atrophic hair follicles in clinical trials. 8 New treatments include stem cells and their products, 9 peroxidases, 10 prostaglandin derivatives, 11 Chinese medicine molecules, 12 and photoelectric therapy, 13 all of which mediate hair follicle regeneration by regulating apoptosis. The stability and regulatory mechanisms of the above treatments remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%